2021
DOI: 10.21203/rs.3.rs-409856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevation of Systemic Defense in Potato Against Alternaria Solani by a Consortium of Compatible Trichoderma Spp.

Abstract: The crop loss due to phytopathogens is a serious problem affecting the entire world. To avoid economic losses due to phytopathogens synthetic chemicals have been used for years generating serious concerns about the human health and environment. Today the use of beneficial microorganisms to treat phytopathogens is gaining attention. In this way, Trichoderma spp. has been used for combating plant diseases and inducing defense response in plants. With this idea in mind, in this study we evaluate the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Under infection stress, the application of volatile organic compounds released from the T. viride significantly reduced the Sclerotium rolfsii infection and improved the plant growth as well as increasing the enzyme activities including PAL, PPO, β-1,3-glucanase, and the chitinases content of okra, which stimulated resistance and decreased cell death [ 78 ]. Similarly, Kumar et al [ 79 ] recorded significant increases in the defense enzyme activity of PAL and total phenols in potato leaves resulting from seed tubers treated with T. viride , T. harzianum, and their combination under an infection challenge with Alternaria solani . Without infection stress, Dildey et al [ 80 ] reported an acute increase in the PAL activity of P. vulgaris leaf tissue resulting from seeds treated with T. virens TM3, compared to the control.…”
Section: Discussionmentioning
confidence: 95%
“…Under infection stress, the application of volatile organic compounds released from the T. viride significantly reduced the Sclerotium rolfsii infection and improved the plant growth as well as increasing the enzyme activities including PAL, PPO, β-1,3-glucanase, and the chitinases content of okra, which stimulated resistance and decreased cell death [ 78 ]. Similarly, Kumar et al [ 79 ] recorded significant increases in the defense enzyme activity of PAL and total phenols in potato leaves resulting from seed tubers treated with T. viride , T. harzianum, and their combination under an infection challenge with Alternaria solani . Without infection stress, Dildey et al [ 80 ] reported an acute increase in the PAL activity of P. vulgaris leaf tissue resulting from seeds treated with T. virens TM3, compared to the control.…”
Section: Discussionmentioning
confidence: 95%